Animasi Aset Permainan “Safe Space” Sebagai Edukasi Pencegahan Kekerasan Terhadap Anak - Rizkika, Septiana; Santika, Khofifah Rahardiyah; Prasetya, Happy Yugo (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
Violence against children remains a serious issue that continues to occur in many environments. Unfortunately, there is still a lack of effective visual educational media that help children recognize signs of danger or unsafe situations. Children need learning tools that are engaging, easy to understand, and appropriate for their developmental stage. Therefore, this study focuses on the design and development of two-dimensional animation assets for an educational game titled “Safe Space” as a medium for educating children about violence prevention. This research employs a product creation method, emphasizing the visual design and 2D animation production processes that support the game's content. The stages in this method include observation, concept formulation, character and environment design, and animation production. The process is divided into pre-production, production, and post-production phases, which involve client brainstorming in pre-production, creation of 2D vector assets and animation using the cut-out technique during production, and rendering in post-production for game implementation. The final result of this project includes animated movements such as idle, jump, run, walk, slide, and fall, rendered as image sequences to be used as assets in the “Safe Space” educational game. These animations were created using the cut-out technique with the aid of Adobe Illustrator and Adobe After Effects. It is expected that the resulting animation will serve as an interactive and informative educational tool, helping children better understand preventive actions against violence.